(untitled) (Irrigation and Melioration, 2026)
This article investigates the principles of ensuring hydraulic balance between the flow section and impellers of centrifugal pumps and hydroelectric power plants. The flow characteristics along the spiral chamber (volute) of the centrifugal pump casing were studied, and a mathematical model was developed based on the provided drawings and dimensions. Hydraulic formulas for determining the cross-sectional area by angle, flow rate distribution, and radial expansion coefficients of the spiral chamber are presented. Based on the specific variant values for the polar coordinates (from 0° to 360°) shown in the figure, the spiral radius were calculated and their drawings were created in COMPAS-3D software. Additionally, the manifestation of centrifugal force in the system is physically substantiated through Euler’s equations and pressure gradients. The prospects of using modern composite materials to increase the cavitation and erosion resistance of pumping station equipment are analyzed.